2014
DOI: 10.1111/aec.12206
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale impacts on avian biodiversity due to a despotic species, the bell miner (Manorina melanophrys)

Abstract: Bell miners (Manorina melanophrys; Meliphagidae) are a highly social and very aggressive honeyeater. They are despotic and cooperate in the defence of their territories against other bird species, leading to the almost complete exclusion of other avifauna from miner-occupied regions. This study aimed to resolve some of the fine-scale effects of bell miner aggression on avian diversity both within and adjacent to colonies to determine the true impact of a colony on local avifaunal abundance. Three areas, distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In this study it was observed being given by adult birds, where the call did not elicit feeding, but likely served as a form of contact vocalisation that acoustically linked visually separated colony members. Alternatively, it may be used as a heterospecific 'warning' indicating an area occupied by Noisy Miners, similar to the likely function of the 'tink' vocalisations of Bell Miners (Heathcote 1989), as both species are highly despotic (Mac Nally et al 2012;Leseberg et al 2015). This possibility warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study it was observed being given by adult birds, where the call did not elicit feeding, but likely served as a form of contact vocalisation that acoustically linked visually separated colony members. Alternatively, it may be used as a heterospecific 'warning' indicating an area occupied by Noisy Miners, similar to the likely function of the 'tink' vocalisations of Bell Miners (Heathcote 1989), as both species are highly despotic (Mac Nally et al 2012;Leseberg et al 2015). This possibility warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The endemic colonial Honeyeater genus, Manorina, is foremost among the threats represented by overabundant native birds in Australia. Three of the four species in the genus have become overabundant since European settlement and have negative impacts on other native birds due to extreme interference competition (Mac Nally et al 2012, Leseberg et al 2014, Kutt et al 2016. The Noisy Miner is particularly problematic because of its hyper-aggressive competitive behavior and unique effectiveness in structuring avian assemblages at a subcontinental scale in remnant woodland habitat in heavily cleared agricultural landscapes (Dow 1977, Maron et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Native Manorina honeyeater species are strong competitors within the extensive Australian woodland systems, with bell miners ( Manorina melanophrys ), yellow‐throated miners ( Manorina flavigula ), and noisy miners ( Manorina melanocephala ) implicated in the widespread decline in small woodland birds (Kutt, Vanderduys, Perry, Mathieson, & Eyre, ; Leseberg, Lambert, & McDonald, ; Maron et al., ). The presence of noisy miners (Figure ) has increased substantially in nine bioregions across eastern Australia (and decreased in none) since 1998 (Maron et al., ), and it is likely that the species is more common now than ever before, given the substantially altered landscape and habitat structure throughout these regions (Thomson et al., ).…”
Section: Introductionmentioning
confidence: 99%